Expression and Clinical Significance of CMTM6 and PD-L1 in Triple-Negative Breast Cancer. (7th July 2022) - Shi, Shuai; Ma, Hong-Yan; Sang, Yin-zhou; Ju, Ying-Bo; Liu, Xiao-Yun; Zhang, Zhi-Gang
Abstract : The CKLF-like MARVEL transmembrane domain containing 6 ( CMTM6 ) plays an extremely important role of the programed death receptor ligand-1 ( PD-L1 ) protein. Our study is aimed at investigating the expression of CMTM6 and PD-L1 proteins in triple-negative breast cancer and their correlation with the clinical pathological data of patients. We selected 89 cases of triple-negative breast cancer and 62 cases of normal breast tissue specimens. Immunohistochemical methods were used to detect the expression levels of CMTM6 and PD-L1 and to carefully study differences in their expression. The expression of CMTM6 and PD-L1 in TNBC was higher than that in normal breast tissue, and the expression of the two was positively correlated (p < 0.05 ). In TNBC, CMTM6 expression is positively correlated with tumor size, lymph node metastasis, Ki67 proliferation index, and TNM stage (p < 0.05 ). PD-L1 expression is positively correlated with tumor size, lymph node metastasis, Ki67 proliferation index, TNM stage, and vascular infiltration (p < 0.05 ). Kaplan-Meier analysis showed that the positive expression of CMTM6 and PD-L1 had no correlation with the survival rate of patients (p > 0.05 ). According to KM-plotter, we found that a higher CMTM6 expression was positively related with relapse-free survival rate of patients (p < 0.05 ). A higher PD-L1 expression was positively correlated with relapse-free, overall, and distant metastasis survival rate of patients (p < 0.05 ). In timer database, we found a positive correlation between the expression of CMTM6 and PD-L1 in triple-negative breast cancer. Both CMTM6 and PD-L1 are highly expressed in TNBC, and their expressions are positively related. In the future, the two gene might become targets for the treatment of TNBC, providing a basis of clinical treatment of TNBC.